Analisis A Debt-For-Nature Swap Sebagai Alternatif Mengurangi Utang Indonesia Kepada Luar Negeri - Hinsa Siahaan (The Winners, 2006)
Given the size of Indonesia’s foreign debt and the rate of forest destruction, “a debt-for-nature swaps” seems an obvious solution. In these schemes, a portion of a nation’s public debt is bought by a third party at substantial discount. The debt then iscancelled. In return, the country promise to protect severall million hectares of forests. This research focused on dicussion of the possibility of the Government of The Republic of Indonesia to reduce its foreign debt by using a debt-for-nature swap.